Determinants of modern family planning methods in Ethiopia: A community-based, cross-section mixed methods study - Hocheol Lee; Eshetu Girma Kindane; Young Ah Doh; Eun Woo Nam (Dialogues in Health, 2022)
In 2019, Ethiopia had a total fertility rate of 4.2 births per woman with the rates varying significantly across regions. The Federal Ministry of Health of Ethiopia announced “Ethiopia FP 2020” to address the high fertility rate, aiming to reduce it to 3.0 by 2020. This study aimed to identify the determinants of the use of modern family planning services in the Amhara, Oromia, and Somali regions. A community-based, cross-sectional mixed methods study was conducted, using quantitative and qualitative surveys. The quantitative survey data were subjected to binary logistic regression analyses. Participants included over 4117 married men and women aged 15–65 years old. This study found that participants in Oromia were 8.673 times more likely to have modern family planning methods than those in Somali. Participants in Amhara were 5.183 times more likely to have modern family planning methods than their Somali counterparts. Women, married respondents, and recipients of media messages were more likely to have family planning experience. Family planning discussions with health extension workers and health professionals played a significant role in modern family planning. These findings show that establishing a family planning strategy that considers the sociocultural characteristics of each region help address regional contexts. Everyone in Somali—especially husbands and religious leaders—must be educated in family planning and funds be made available to deploy advanced measures for the same.